Penerapan Sistem Bagi Hasil Budidaya Madu Ditinjau Dari Etika Bisnis Islam Di Desa Rantau Karya Kecamatan Geragai Kabupaten Tanjabtim - WILLYARDO ONEJA; PUTRI APRIA NINGSIH; NOVA ERLIYANA (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The community of Rantau Karya Village is a community of which some are breeders, especially in the Honey Cultivation sector which is owned by the community of Rantau Karya Village, Geragai District, Tanjabtim Regency. With this honey cultivation, the community can fulfill their daily needs. The purpose of this research is to find out how the profit sharing system is implemented in the cooperation between owners and managers of honey cultivation in Rantau Karya Village, Geragai District, Tanjabtim Regency and to find out how Islamic business ethics reviews the implementation of the profit sharing system for honey bee cultivation in Rantau Karya Village. In this research, the method used is a qualitative method by checking the validity of the data using triangulation techniques and data collection methods using observation, interviews and documentation. The informants in this research are the owners and managers of honey cultivation. The application of the profit sharing system in the Mudharabah contract in honey cultivation in Rantau Karya Village is as Mudharib who carries out an activity or business and the owner is as shahibul maal who entrusts the cultivation to the manager to manage. Every time the harvest season arrives every 2 weeks, the owner shares the honey basil with the manager. 70% owner and 30% manager, that is the initial agreement between the owner and manager that has been agreed upon by both parties. So the author analyzes that, basically if all profit sharing activities are carried out correctly and in accordance with what Islam teaches then the profit sharing can be said to be valid, but if the profit sharing activities are not carried out correctly and are contrary to what Islam teaches, then for these results can be said to be invalid. If it is related to honey cultivation in Rantau Karya Village, Geragai District, Tanjabtim Regency, in its implementation it can be said to be in accordance with the principles of Islamic business ethics in accordance with the characteristics of the Prophet, namely (Siddiq, Tabligh, Amanah, Fathanah).